2022
DOI: 10.15452/cejnm.2022.13.0024
|View full text |Cite
|
Sign up to set email alerts
|

Challenges experienced by nurses caring for patients from different cultures: a scoping review of the literature, 2010-2020

Abstract: Aim: Increased cultural diversity due to global migration and on-going associated healthcare disparities has highlighted the importance of culturally competent care. We sought to summarize existing knowledge and identify gaps in research linked to the cultural challenges encountered by nurses when caring for patients from different cultures. Design: A scoping review. Methods: Informed by PRISMA-ScR guidelines, we searched PubMed, ScienceDirect, EBSCO Host, Web of Science, and Google Scholar using relevant MeSH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…The study showed that language barriers, inadequate communication, ineffective time management, and cultural impacts on patient health education are the main challenges nurses face while teaching patients. Similar factors stated in other studies that influence the practice of patient education include adequate time and workplace culture, language barriers, and poor communication [13].…”
Section: Open Journal Of Nursingsupporting
confidence: 70%
“…The study showed that language barriers, inadequate communication, ineffective time management, and cultural impacts on patient health education are the main challenges nurses face while teaching patients. Similar factors stated in other studies that influence the practice of patient education include adequate time and workplace culture, language barriers, and poor communication [13].…”
Section: Open Journal Of Nursingsupporting
confidence: 70%
“…These challenges include staff shortages, the demands of their roles, and a lack of time which can negatively affect RNs‐patient communication (Carvajal et al, 2019 ; Hussin et al, 2018 ). Additionally, a scoping review by Červený et al ( 2022 ) highlighted the challenges experienced by nurses when caring for patients from different cultures. The review identified understanding religion, psychosocial emotions, culture and spirituality as key aspects of providing high‐quality end‐of‐life care.…”
Section: Introductionmentioning
confidence: 99%